Integrating Augmented Reality into Problem-Based Learning: Effects on Elementary School Students' Critical Thinking in Science - Yuni Krisnawati; Sandra Arhesa; Hos Arie Rhamadhan Sibarani; Ady Akbar; Achmad Salido (Universitas Pendidikan Mandalika, 2026)
Developing students' critical thinking skills has become an increasingly important educational priority in the era of artificial intelligence. Despite the growing use of Augmented Reality (AR) in education, empirical evidence regarding its effectiveness in fostering elementary school students' critical thinking in science remains limited, particularly when integrated with Problem-Based Learning (PBL). This study investigated the effect of AR-assisted PBL on elementary students' critical thinking skills in science. A quasi-experimental design with a non-equivalent pretest–posttest control group was employed involving 62 fifth-grade students (experimental group = 32; control group = 30). Both groups received identical problem-based science instruction on flora and fauna topics, while AR was integrated only into the experimental group. Students' critical thinking skills were assessed using an essay-based instrument developed according to the RED framework (Recognizing Assumptions, Evaluating Arguments, and Drawing Conclusions). Descriptive statistics and inferential analyses were conducted using an independent-samples t-test for the pretest and a one-tailed Mann–Whitney U test for the posttest. The findings revealed that students receiving AR-assisted PBL achieved significantly higher critical thinking scores than those receiving problem-based learning without AR (posttest mean = 81.72 vs. 75.83; p = 0.005), with a moderate educational effect (r = 0.329). These findings suggest that integrating interactive three-dimensional visualization within a problem-based learning environment facilitates scientific reasoning and supports the development of critical thinking beyond conceptual understanding alone. This study contributes to the growing literature on technology-enhanced science education by providing empirical evidence that AR functions most effectively as a pedagogical tool when embedded within inquiry-oriented learning environments. The findings also offer practical implications for designing more interactive and student-centered science instruction in elementary schools.